2020
DOI: 10.1038/s41598-020-61388-2
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion between P. falciparum infected erythrocytes and human endothelial receptors follows alternative binding dynamics under flow and febrile conditions

Abstract: characterizing the adhesive dynamics of Plasmodium falciparum infected erythrocytes (IEs) to different endothelial cell receptors (ECRs) in flow is a big challenge considering available methods. This study investigated the adhesive dynamics of IEs to five ECRs (CD36, ICAM-1, P-selectin, CD9, CSA) using simulations of in vivo-like flow and febrile conditions. To characterize the interactions between ECRs and knobby and knobless IEs of two laboratory-adapted P. falciplarum isolates, cytoadhesion analysis over ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 54 publications
(86 reference statements)
2
21
0
1
Order By: Relevance
“…Since Var2CSA is one of∼60 PfEMP1 variants, with only one expressed in a parasite at any given time, we wanted to test whether FIKK4.1 is important for trafficking other PfEMP1 variants. To do so, we selected for binding to other endothelial cell receptors by panning over CD36-expressing CHO cells (49). Treatment of these FIKK4.1 cKO parasites with rapamycin results in a 51.5 ± 13% reduction in cytoadhesion under flow to CHO cells expressing CD36 (Figure 5C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Var2CSA is one of∼60 PfEMP1 variants, with only one expressed in a parasite at any given time, we wanted to test whether FIKK4.1 is important for trafficking other PfEMP1 variants. To do so, we selected for binding to other endothelial cell receptors by panning over CD36-expressing CHO cells (49). Treatment of these FIKK4.1 cKO parasites with rapamycin results in a 51.5 ± 13% reduction in cytoadhesion under flow to CHO cells expressing CD36 (Figure 5C).…”
Section: Resultsmentioning
confidence: 99%
“…Cytoadhesion assay EPCR/ICAM1-binding iRBCs were obtained via magnetic enrichment of dual-binding iRBCs with ProteinA-coupled Dynabeads (Invitrogen), which were associated to anti-EPCR/ICAM1-binding PfEMP1 antibodies (a kind gift from Anja Jensen, University of Copenhagen) as described previously (64). Late trophozoites were selected for CD36 binding by incubating percoll-enriched iRBCs with CD36-CHO cells for 1 h at 37 °C as previously described (49). Adherent cells were kept in culture after 5 x washing with RPMI.…”
Section: Generation Of Parasite Linesmentioning
confidence: 99%
“…Based on this and our findings we hypothesize that parasites circulating in severely ill patients are younger due to the expression of EPCR-/ICAM-1-binding Pf EMP1 variants, whereas parasites in non-severe patients may circulate longer due to their expression of Pf EMP1 binding to CD36. Although affinity of the CIDR domains to each of these receptors was shown to be similar with median Kd values of 12 nM for CD36 (Hsieh et al, 2016) and 16.5 nM for EPCR (Lau et al, 2015), recent papers describe a rolling binding phenotype of infected red blood cells over CD36 and a static binding for EPCR and ICAM-1 under flow conditions (Lubiana et al, 2020; Bernabeu et al, 2019; Dasanna et al, 2017; Herricks et al, 2013). Due to their biconcave shape trophozoites seem to roll faster but less stable by flipping over CD36-expressing cells, whereas schizonts roll over longer distances at different shear stresses applied.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, "knobby" (cellular-protrusionbearing) erythrocytes infected with Plasmodium falciparum (an organism frequently responsible for malarial infection) displayed greater temperature-dependent binding to ECs than "knobless" erythrocytes infected with the same pathogen. Rather than a simple physical advantage in cell-cell binding, the proadhesive effect of the presence of knobs may reflect a localized abundance of adhesive ligands and receptors (Lubiana et al, 2020). Interestingly, Leal Denis and coworkers demonstrated that the export of ATP by RBCs made to adhere to coverslips coated with poly-D-lysine was far greater than that of RBCs on uncoated coverslips (Leal Denis et al, 2013).…”
Section: Atp Export From Red Blood Cells Couples Deformability and Modulation Of Adhesivitymentioning
confidence: 99%